Efforts of Religious Leaders in Building Attitude of Religious Moderation in the Village of Pada Nubatukan Lembata, East Nusa Tenggara - Burhan, Syarifudin; Haris, Abdul; Yazid, Syamsurizal (International Journal of Education, Culture, and Society, 2025)
This study aims to describe the efforts of religious leaders in building religious moderation attitudes in villages in terms of the role of religious leaders and obstacles and challenges. This research uses a qualitative approach with a case study type. The data was collected through observation, interviews and documentation, and analyzed using Miles and Huberman interactive techniques. The validity of the data was tested using source and technical triangulation techniques. The results of the study show that the efforts of religious leaders in building religious moderation attitudes in various ways such as; Open dialogue, socialization activities, and deliberations, however, religious leaders also experience obstacles and challenges such as; the influence of social media and the lack of religious understanding.